Pengendalian Persediaan Batubara Menggunakan Metode Economic Order Quantity (EOQ) (Studi Kasus : PT. Indah Kiat Pulp & Paper tbk) - denny astrie anggraini; Rudy (Jurnal Surya Teknika, 2021)
PT. Indah Kiat Pulp and Paper Perawang Mill is one of the largest pulp and paper producing companies in Indonesia and even in Southeast Asia. This company produces its own energy for production purposes. Where this company has 12 Steam Power Plants (PLTU) with a boiler system. This Steam Power Plant (PLTU) uses several types of fuel, both biomass and fossil fuel types. The main fuel used is the type of fossil coal. However, currently the coal inventory control process has not been carried out properly so that a lot of coal is piled up in the stockpile and causes coal to burn (Spontanous Comustion). In order not to cause losses to the company, the control of coal inventory must be carried out properly. One method that can be used is the Economic Order Quantity (EOQ) method for 12 periods (1 year) namely December 2020 – November 2021. From the results of this inventory control, the number of economic orders for coal is 20,841 tons with a total of 107 orders. To avoid stockpiling or shortages, a safety stock is needed, namely 847,439 Tons, while reordering can be done when the coal stock in the stockpile is 522,155 Tons remaining. With maximum stock in stockpile is 868,820 Tons. The total cost for coal inventory that must be spent is Rp. 23,244,747. Keywords : Coal, Inventory Control, Economic Order Quantity (EOQ)